SAT0230 The Minimum Clinically Important Improvement and Patient Acceptable Symptom State in Basdai and Basfi in Patients with Ankylosing Spondylitis. (23rd January 2014) - Kviatkovsky, M. J.; Ramiro, S.; Landewé, R.; Tubach, F.; Dougados, M.; van der Heijde, D.
Abstract : Background: The minimum clinically important improvement (MCII) and patient acceptable symptom state (PASS) are clinically relevant measures that report the patient condition. These can be established using cutoffs in BASDAI and BASFI to assess disease activity and functional disability respectively, in patients with Ankylosing Spondylitis (AS). Objectives: To estimate the MCII and PASS cutoff values for BASDAI and BASFI for patients with AS. Methods: A multinational (Australia, France, Italy, Lebanon, Morocco, Spain and The Netherlands) cohort study was conducted where patients with AS received NSAIDs for 4-weeks. PASS and MCII were determined using external anchor questions for patient global assessment for BASDAI and functional impairment for BASFI. For PASS patients were asked to consider the ways AS has affected them during the last 48 hours and if this would be an acceptable state for the rest of their life. Patients who answered "acceptable" met criteria for PASS analysis. For MCII, patients were asked first to compare how they felt in the past 48 hours to how they felt at the start of the study. Secondly, if they felt improved, to consider how important the improvement was. Patients who reported improvement that was either moderate or slightly important met criteria for MCII analysis. Analyses were conducted using patients who met criteria based on the external anchor question and for comparison, also in patients who met the general rheumatic disease criteria published in the REFLECT study. These criteria recommend a value <4 for PASS and relative improvement ≥20% for MCII.(1 ) The 75th percentile approach was used to establish cutoff values of MCII and PASS in BASDAI/ BASFI. Results: Of 283 patients with AS, 214 were males (76%), 181 were HLA-B27 positive (64%) with a mean age of 42.9 years (13.5) and mean disease duration of 12.9 (9.7) years. PASS values were 4.1 for BASDAI and 3.8 for BASFI (Table ). Both values were slightly lower in patients selected using REFLECT study cutoffs. The MCII in BASDAI was 0.7 for absolute and 16.7% for relative change and slightly higher using REFLECT study cutoffs. The MCII in BASFI was set 0.4 for absolute 8.7% for relative change with similar values found using REFLECT study cutoffs. Conclusions: These disease specific PASS and MCII cut off values allow researchers and clinicians to use validated outcome measure instruments to dichotomize patients into those who achieve therapeutic success and those who do not. References: Tubach et al, AC&R 2012. Disclosure of Interest: None Declared